Respuesta :

Answer:

Answer:

4.

First you need to assume X not equal to 3 or -3. These values would make the denominator invalid.

Because,

X - 3 must not be 0

X + 3 must not be 0

X^2 - 9 must not be 0

Then, you would have:

     1/(X-3) + 2/(X+3) = 1/(X^2-9)

<=> [ X+3 + 2*(X-3) ]/(X^2-9)=1/(X^2-9) (*)

(Note that: (X-3)(X+3) = X^2-9)

Cancel out the denominator of both side of (*), then we have

X+3 + 2*(X-3) = 1

<=> X+3+2X-6=1

<=> 3X =4

<=> X = 4/3 (this value satisfies our first assumption)

=> X = 4/3 is the solution

5.

First you need to assume X not equal to 5 or 0. These values would make the denominator invalid.

Because,

X - 5 must not be 0

2X must not be 0

3X^2-15X = 3X(X-5) must not be 0

Then, you would have:

[2*2X + X-5]/[(X-5)*2X] = 5/[3X*(X-5)]

<=> (5X-5)/[(X-5)*2X] = 5/[3X*(X-5)]

<=> 3*(5X-5)/[(X-5)*6X] =2*5/[6X*(X-5)] (*)

Cancel out the denominator of both side of (*), then we have

3*(5X-5)=2*5

<=> 15X-15=10

<=> 15X =25

<=> X =25/15 =5/3 (this value satisfies our first assumption)

=> X = 5/3 is the solution